2022
DOI: 10.1002/ncp.10831
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in anthropometric measures and gastrointestinal tolerance in patients with cystic fibrosis by using a digestive enzyme cartridge with overnight enteral nutrition

Abstract: Background: Patients with cystic fibrosis (CF) and pancreatic insufficiency are at risk for suboptimal fat absorption, inability to maintain weight, poor growth, and increased gastrointestinal (GI) symptoms due to malabsorption. Enteral nutrition (EN) is used to supplement caloric intake and requires pancreatic enzyme replacement for effective digestion. We evaluated the relationship between long-term use of an in-line digestive enzyme cartridge with EN and changes in anthropometric measures and GI symptoms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The findings of this study are consistent with previous findings, strongly supporting the clinical benefit for patients receiving nocturnal feedings to use the in-line lipase cartridge as the most appropriate source of PERT therapy to help bolster growth. 11,14 Height significantly increased after the use of in-line lipase cartridge. Adequate linear growth is observed early in the life of people with CF, and poor linear growth early in life is associated with stunted height in adults with CF.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The findings of this study are consistent with previous findings, strongly supporting the clinical benefit for patients receiving nocturnal feedings to use the in-line lipase cartridge as the most appropriate source of PERT therapy to help bolster growth. 11,14 Height significantly increased after the use of in-line lipase cartridge. Adequate linear growth is observed early in the life of people with CF, and poor linear growth early in life is associated with stunted height in adults with CF.…”
Section: Discussionmentioning
confidence: 97%
“…11 Another similar study performed by Hendrix et al in 2022, saw an initial jump in patients' BMI followed by a return to baseline, which suggests an increase in weight over height. 14 Unfortunately, because of the nature of the study, the effect of exacerbations or complications of patients' underlying diagnoses on anthropometric changes were not analyzed. Anthropometric data collected for analysis were the measurements at every 3-month, standard-of-care visit.…”
Section: Discussionmentioning
confidence: 99%
“…An evidence-based review found “insufficient evidence to make a recommendation regarding the association of specific PERT dosing and CFA or growth” [ 21 ]. Although not contemporaneously studied, use of an in-line lipase cartridge, which has been shown to be associated with improvements in plasma DHA and EPA absorption relative to placebo, has been shown to lead to improved BMI and GI symptoms when used over one year [ 22 ]. Use of this in-line lipase cartridge was also associated with increases in red blood cell (RBC) membrane DHA and EPA over 90 days [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Feeding by gastrostomy continues to be utilized as a tool to address malnutrition when present. The addition of digestive enzyme cartridge uses in tandem with overnight enteral nutrition was associated with improvement in both anthropometrics in children and adults, as well as reduced GI symptoms [17]. While malnutrition may continue to decrease with further care development, these studies highlight refinement in available tools.…”
Section: Undernutritionmentioning
confidence: 91%